2017
DOI: 10.1016/j.foreco.2017.05.030
|View full text |Cite
|
Sign up to set email alerts
|

New insights on above ground biomass and forest attributes in tropical montane forests

Abstract: 23Despite the potential of tropical montane forests to store and sequester substantial amounts of 24 carbon, little is known about the above ground biomass (AGB) and the factors affecting it in 25 these ecosystems, especially in Africa. We investigated the height-diameter allometry, AGB, 26 and related differences in AGB to taxonomic and structural forest attributes in three distinct 27 forest types (dry, mixed species and elfin) in three mountains of northern Kenya. We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 58 publications
3
19
1
2
Order By: Relevance
“…However, we also found that Michaelis–Menten models performed better on average than Weibull models (in terms of reducing height prediction error) when sample sizes were small, with the relative performance of Weibull models increasing with sample size. The failure of a single model form to consistently outperform others at minimising height prediction errors (Figure ) supports previous studies that have found that the best performing model form varies between forest types (Cuni‐Sanchez et al., ). For example in locations with frequent natural disturbances trees may not reach their asymptotic maximum heights, and in these plots log–log models may perform better than asymptotic models.…”
Section: Discussionsupporting
confidence: 86%
“…However, we also found that Michaelis–Menten models performed better on average than Weibull models (in terms of reducing height prediction error) when sample sizes were small, with the relative performance of Weibull models increasing with sample size. The failure of a single model form to consistently outperform others at minimising height prediction errors (Figure ) supports previous studies that have found that the best performing model form varies between forest types (Cuni‐Sanchez et al., ). For example in locations with frequent natural disturbances trees may not reach their asymptotic maximum heights, and in these plots log–log models may perform better than asymptotic models.…”
Section: Discussionsupporting
confidence: 86%
“…Those plots with dominance of Polylepis pauta and lower prevalence of Baccharis padifolia had a positive relationship with higher AGB-C gains. These results suggest the importance large-statured trees, community species composition and their abundances in controlling C of dynamics as previously reported for high tropical and lowlands forests [84,[89][90][91][92]. Further explanation of these differential sequestration rates may be related to the recent heterogeneous human impact that each plot experienced.…”
Section: Plos Onesupporting
confidence: 81%
“…La biomasa forestal se define como el material lignocelulósico generado por procesos metabólicos de las plantas arbóreas (Simangunsong et al, 2017), dicho material se caracteriza por tener una composición con gran potencialidad energética que permite, mediante procesos de combustión completa o incompleta, la generación de calor y energía que puede ser transformada en electricidad (Cuni-Sanchez et al, 2017). La ventaja de la biomasa arbórea sobre otras fuentes energéticas es que es renovable, permite hacer un ciclo continuo de absorción de emisiones de CO 2 , la tecnología que implementa es de bajo costo y la cosecha de la biomasa es en el corto plazo (Simangunsong et al, 2016;Cuni-Sanchez et al, 2017). Adicionalmente, contribuye al balance de carbono y a la utilización y rehabilitación de tierras de bajo valor productivo.…”
Section: Introductionunclassified